2019
DOI: 10.3390/ma12233839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vanadium on the Microstructure of IN718 Alloy by Laser Cladding

Abstract: A deleterious Laves phase forms in the solidified structure of Inconel 718 (IN718) alloy during laser cladding. However, effective removal methods have not yet been identified. In this study, we first added the IN718 alloy cladding layers with a trace amount of vanadium (V, 0.066 wt.%). Then, we studied the solidification structure of cladding layers using a confocal laser scanning microscope and scanning electron microscopy. The microstructure and Laves phase morphology were investigated. The distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The finite element study [35][36][37] was carried out under the loads of 100, 200, 300, 400, 500, and 600 N, respectively, and the rotating speed of the ring was 2000 r/min. The maximum surface temperature and radial diffusion size of the ring under different loads were obtained (Figure 5).…”
Section: Fepg and Test Resultsmentioning
confidence: 99%
“…The finite element study [35][36][37] was carried out under the loads of 100, 200, 300, 400, 500, and 600 N, respectively, and the rotating speed of the ring was 2000 r/min. The maximum surface temperature and radial diffusion size of the ring under different loads were obtained (Figure 5).…”
Section: Fepg and Test Resultsmentioning
confidence: 99%
“… ( a ) Morphology of V powder (1000×), ( b ) morphology of IN718 alloy power (200×), ( c ) SVW80C-3D hybrid additive and subtractive machine center, ( d ) Vickers hardness measurements points [ 16 ]. …”
Section: Figurementioning
confidence: 99%
“…In our previous research [ 16 ], the addition of vanadium was shown to have a positive effect on the microstructure uniformity, Lave phase distribution and mechanical properties of the IN718 alloy. Hence, we studied the effects caused by the addition of 0.081–1.88 wt.%, by weight, of vanadium into IN718 alloy on the microstructure and mechanical properties of the laser cladding.…”
Section: Introductionmentioning
confidence: 99%
“…The distinctive advantages of AM are that it can be used to produce innovative, complex designs and the fact that it is lightweight compared to conventional subtractive or casting manufacturing. Owing to these advantages, this manufacturing method has been actively studied in various fields [5][6][7]. A current major concern is manufacturing defects that can occur in the interior of AM parts and their effects on the integrity of these parts [8,9].…”
Section: Introductionmentioning
confidence: 99%